A Peculiar ICME Event in August 2018 Observed With the Global Muon Detector Network. Issue 3 (22nd February 2021) - Kihara, W.; Munakata, K.; Kato, C.; Kataoka, R.; Kadokura, A.; Miyake, S.; Kozai, M.; Kuwabara, T.; Tokumaru, M.; Mendonça, R. R. S.; Echer, E.; Lago, A. Dal; et al.
Abstract: We demonstrate that global observations of high‐energy cosmic rays contribute to understanding unique characteristics of a large‐scale magnetic flux rope causing a magnetic storm in August 2018. Following a weak interplanetary shock on August 25, 2018, a magnetic flux rope caused an unexpectedly large geomagnetic storm. It is likely that this event became geoeffective because the flux rope was accompanied by a corotating interaction region and compressed by high‐speed solar wind following the flux rope. In fact, a Forbush decrease was observed in cosmic‐ray data inside the flux rope as expected, and a significant cosmic‐ray density increase exceeding the unmodulated level before the shock was also observed near the trailing edge of the flux rope. The cosmic‐ray density increase can be interpreted in terms of the adiabatic heating of cosmic rays near the trailing edge of the flux rope, as the corotating interaction region prevents free expansion of the flux rope and results in the compression near the trailing edge. A northeast‐directed spatial gradient in the cosmic‐ray density was also derived during the cosmic‐ray density increase, suggesting that the center of the heating near the trailing edge is located northeast of Earth. This is one of the best examples demonstrating that the observation of high‐energy cosmic rays provides us with information that can only be derived from the cosmic ray measurements to observationally constrain the three‐dimensional macroscopic picture of the interaction between coronal mass ejections and the ambient solar wind, which is essential for prediction of large magnetic storms. Key Points: We derived the spatial distribution of cosmic rays associated with a peculiar interplanetary counterpart of a coronal mass ejection event that caused a large magnetic storm in August 2018 We found a cosmic‐ray density increase possibly resulting from the magnetic flux rope compression by the following faster solar wind The Global Muon Detector Network observed this density increase as a macroscopic modification of this geoeffective flux rope